Combined In Vivo Microdialysis and PET Studies to Validate [11C]Yohimbine Binding as a Marker of Noradrenaline Release - Anne Marlene Landau; Steen Jakobsen; Majken Borup Thomsen; Aage Kristian Olsen Alstrup; Dariusz Orlowski; Jan Jacobsen; Gregers Wegener; Arne Mørk; Jens Christian Hedemann Sørensen; Doris J. Doudet (Biomolecules, 2023)
The noradrenaline system attracts attention for its role in mood disorders and neurodegenerative diseases but the lack of well-validated methods impairs our understanding when assessing its function and release in vivo. This study combines simultaneous positron emission tomography (PET) and microdialysis to explore if [11C]yohimbine, a selective antagonist radioligand of the α2 adrenoceptors, may be used to assess in vivo changes in synaptic noradrenaline during acute pharmacological challenges. Anesthetised Göttingen minipigs were positioned in a head holder in a PET/CT device. Microdialysis probes were placed in the thalamus, striatum and cortex and dialysis samples were collected every 10 min. Three 90 min [11C]yohimbine scans were acquired: at baseline and at two timepoints after the administration of amphetamine (1–10 mg/kg), a non-specific releaser of dopamine and noradrenaline, or nisoxetine (1 mg/kg), a specific noradrenaline transporter inhibitor. [11C]yohimbine volumes of distribution (VT) were obtained using the Logan kinetic model. Both challenges induced a significant decrease in yohimbine VT, with time courses reflecting their different mechanisms of action. Dialysis samples revealed a significant increase in noradrenaline extracellular concentrations after challenge and an inverse correlation with changes in yohimbine VT. These data suggest that [11C]yohimbine can be used to evaluate acute variations in synaptic noradrenaline concentrations after pharmacological challenges.